Pilot study: do obese compared to lean women experience greater body dissatisfaction in the postnatal period?. (18th April 2012) - Keely, A; Swanson, V; Denison, F
Abstract : Background: We hypothesised that obese women would experience greater body dissatisfaction within 72 hours postpartum and 6-8 weeks postnatal compared to lean women. Aims: To compare levels of body dissatisfaction in obese compared to lean women during the postnatal period. Method: Obese (BMI >30kg/m2) and lean (BMI 18.5-25kg/m2) women who were breastfeeding at hospital discharge were recruited within 72 hours of delivery. Demographic details collected included age, socio-economic status, parity and mode of delivery. Participants completed a questionnaire, prior to hospital discharge (timepoint (TP) 1) and at 6-8 weeks postnatal (TP2). Using Multidimensional Body-Self Relations Questionnaire Appearance (MBSRQ) scales, body image was categorised as: appearance evaluation (AE): appearance orientation (AO): body areas satisfaction (BAS): overweight pre-occupation (OP): self-classified weight (SCW). Data were analysed by descriptive statistics and unpaired t-tests. Results: Of 110 women recruited at TP1, 83.7% (41/49) obese women and 73.8% (45/61) non-obese women returned both questionnaires. Mean ages were 30.7 in the obese group, 33 in the lean group. Obese women scored more negatively (mean (SD)) compared to lean women at both timepoints for all MBSRQ scales except AO: AE 2.7(0.8) vs 3.5(0.5)(p<0.001) TP1, 2.6(0.5) vs 3.2(0.6)(p<.0001) TP2: BAS 2.9(0.6) vs 3.7(0.4)(p<.001) TP1, 2.8(0.5) vs 3.4(0.6)(p<.0001) TP2: OP 3.1(0.6) vs 2.7(0.4)(p.001) TP1, 3.2(0.6) vs 2.9(0.5)(p.008) TP2: SCW 1.7(0.5) vs 2.9(0.3)(p<.0001) TP1, 1.7(0.6) vs 2.8(0.4)(p<.0001) TP2. Conclusion: Obese women experience greater body dissatisfaction at < 72 hours postpartum and at 6-8 weeks postnatal compared to lean women. This may influence maternal behaviours such as breastfeeding.